Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Desa Mekar Sari - Claudia, Anggi; Helmi, Tengku Ahmad; Tahir, M. (Universitas Islam Islam Sumatera Utara, 2024)
This research is entitled The Effect of Work Stress and Work Environment on the Performance of Mekar Sari Village Office Employees. The formulation of the problem in this research is to find out whether there is an influence of work stress and the work environment at the Mekar Sari Village Office. This research is a quantitative descriptive research. Data collection techniques were carried out through interviews, questionnaires and documentation studies. The sample in this research was 45 employees. Variables are measured via a Likert Scale. Testing is carried out through validity tests, reliability tests and classical assumption tests. The classic assumption test consists of the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and multiple linear regression test. Hypothesis testing via T test and determination test. The results of this research are that the work stress variable has a negative and significant effect, the work environment variable has a positive and significant effect on the performance of Mekar Sari Village Office employees.